Interpretation of Verbal and Visual Signs in the Converse Shoes Printed Advertisement - Putu Eka Yoga Aditya Pratama; Putu Gede Budiartha (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Abstract This study, entitled "Analysis of Verbal and Visual Signs in Converse Shoe Advertisements," aims to identify and analyze the verbal and visual signs in Converse advertisements. The data was sourced from three printed Converse shoes advertisement found on Pinterest. The analysis is based on Saussure's (1983) and Barthes's (1976) semiotic theories, alongside Cerrato's (2012) theory on color analysis. The study employs a qualitative method, focusing on both image and text analysis. The analysis reveals three main findings: first, each advertisement contains verbal signs that can be analyzed for both denotative and connotative meanings; second, advertisements without verbal signs still convey important messages through visual signs, with images carrying different meanings in line with the context; third, color plays a significant role in reinforcing the messages conveyed through the visuals. The findings highlight that both verbal and visual elements work together to communicate the advertisement’s message effectively. Keywords: verbal, visual, sign, advertisement, Converse